Expert System in Analyzing Stress Levels in Factory Employees Using the Certainty Factor Method - Aya Sofia Dinafa; Abdul Rohman (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Factory employees are jobs that have high enough pressure, therefore they are prone to stress. Employees who experience stress have an impact on reducing productivity. This study aims to design and build to diagnose stress levels in factory employees with the Certainty Factor (CF) method. Data collection is done by means of a mental specialist and the distribution of questionnaires to factory employees. In this technological development, expert systems can be used to prevent employees from experiencing high work stress by identifying it early on so that advice can be given. This system is designed with the PHP programming language and MySQL database. The expert system with the Certainty Factor (CF) method has a fairly high level of accuracy, with a certainty level of 85% and can be a management tool in making decisions related to employee mental health.